LEAF ANATOMY STUDY OF FREYCINETIA SPP. (PANDANACEAE) WITH REFERENCE TO STONE’S INFRAGENERIC CLASSIFICATION - Yessi Santika; Eka Fatmawati Tihurua (PTTI, 2014)
The leaf anatomy of Freycinetia (Pandanaceae) in the Malesian Region is reviewed. We made observations of epidermal tissue, hypodermic and leaf mesophyll for 18 Freycinetia spp. Much variation was seen in the epidermal tissue, e.g., in the existence of papillae, stomata arrangement, shape of epidermis cell and prismatic crystals. We found seven groups within the genus Freycinetia, based on these characters and compared these groups to Stone’s sections.